2019
DOI: 10.1177/1469066718800844
|View full text |Cite
|
Sign up to set email alerts
|

Ligation kinetics as a probe for gas-phase ligand field effects: Ligation of atomic transition metal cations with ammonia at room temperature

Abstract: The kinetics of ammonia ligation to atomic first and second row transition metal cations were measured in an attempt to assess the role of ligand field effects in gas-phase ion-molecule reaction kinetics. Measurements were performed at 295 AE 2 K in helium bath gas at 0.35 Torr using an inductively coupled plasma/selected-ion flow tube tandem mass spectrometer. The atomic cations were produced at ca. 5500 K in an inductively coupled plasma source and were allowed to decay radiatively and to thermalize by colli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Indeed, the observed trends in reaction efficiencies for ammonia addition to first‐ and second‐row atomic transition metal cations are seen to track the values of octahedral LFSE for ammonia ligation across the periodic table (see Figure 6) (Blagojevic et al, 2019b). The LFSE that arises from the interaction of the d‐orbitals of a transition metal ion with the ligand field contributes to the ion/ligand binding energy which in turn determines the kinetics of ion/ligand bond formation.…”
Section: Trends In Ligation Kineticsmentioning
confidence: 81%
See 3 more Smart Citations
“…Indeed, the observed trends in reaction efficiencies for ammonia addition to first‐ and second‐row atomic transition metal cations are seen to track the values of octahedral LFSE for ammonia ligation across the periodic table (see Figure 6) (Blagojevic et al, 2019b). The LFSE that arises from the interaction of the d‐orbitals of a transition metal ion with the ligand field contributes to the ion/ligand binding energy which in turn determines the kinetics of ion/ligand bond formation.…”
Section: Trends In Ligation Kineticsmentioning
confidence: 81%
“…Comparison of measured reaction efficiencies (open squares) at 295 ± 2 K in He bath gas at 0.35 ± 0.01 Torr with experimental (full squares) and theoretical (full circles) binding energies (BE) for the ligation of first‐row atomic transition metal cations with ammonia (Blagojevic et al, 2019b)…”
Section: Trends In Ligation Kineticsmentioning
confidence: 99%
See 2 more Smart Citations
“…A convenient summary of this study can be found at http://www.yorku.ca/dkbohme/research/selection_table.html. It includes studies of the cations of main group, transition metal, and lanthanide elements with O 2 (Koyanagi & Bohme, 2001; Koyanagi et al, 2002), CO 2 (Cheng et al, 2006a; Koyanagi & Bohme, 2006), OCS and CS 2 (Cheng et al, 2006a, 2006b), NO (Blagojevic et al, 2005, 2006), N 2 O (Koyanagi & Bohme, 2001; Lavrov et al, 2004), NO 2 (Jarvis et al, 2010, 2013), CH 4 (Shayesteh et al, 2009), NH 3 (Blagojevic et al, 2019a, 2019b; Koyanagi et al, 2010), D 2 O (Cheng et al, 2006c, 2007), CH 3 F (Koyanagi et al, 2005; Zhao et al, 2006), CH 3 Cl (Zhao et al, 2005), SF 6 (Cheng & Bohme, 2006; Cheng et al, 2009), C 6 H 6 (Blagojevic et al, 2015), C 6 F 6 (Caraiman et al, 2004), and C 5 H 5 N (Blagojevic & Bohme, 2015). In all cases, quantitative rate constants at 295 K and 0.35 Torr of He were obtained for metal cations generated by an inductively coupled plasma (ICP).…”
Section: Introductionmentioning
confidence: 99%